(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article contains theoretical information about the stages of creating a terminological ontological knowledge base, in particular, the ontology development process: specification, conceptualization, formalization and implementation stages. The most popular Ontology languages available today (OWL and RDF), the Protégé editor is about creating a terminological ontological knowledge base, forming a terminological base.